The Value of Stroboscopic Examination in the Diagnosis of Hoarseness - Rasheed, Ahmed M. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:In modem laryngological practice laryngovideostroscopic examination is an important step for correct diagnosis of vocal cord lesions.Aims:To asses the role of laryngovideostroboscopy as a clinical tool in evaluation of hoarse patients.Patients and Methods:Stroboscopic examinations were carried out on 43 patients presented with hoarseness at the ENT department at Al- Kadhimya Teaching Hospital during the period from “January2006 to October 2006".Results:Stroboscopic examination contributed significant diagnostic information, it changed the diagnosis made by nonstroboscopic means in 8 cases (19%), this resulted in avoidanceof surgery in 4 cases and 4 cases referred to surgery instead of medical therapy.Conclusion:Laryngovideostroboscopy is a useful clinical tool in modem laryngoloical practice so as to alter the diagnosis and management plan which may result in avoidance of unnecessarysurgical and /or medical-therapies.